2015
DOI: 10.5657/kfas.2015.0644
|View full text |Cite
|
Sign up to set email alerts
|

Quality Changes and Processing of Fermented Red Snow Crab Chionoecetes japonicus Sauce using Aspergillus kawachii koji

Abstract: This study investigated changes in the quality of fermented red snow crab Chionoecetes japonicus sauce with or without Aspergillus kawachii koji and added salt. Samples were divided into four groups depending on whether koji was added and the amount of salt: RC15, 15% added salt, no koji; RC20, 20% added salt, no koji; RK15, 15% salt plus 10% koji; and RK20, 20% salt plus 10% koji. The samples were fermented at 20±2℃ for 4 months. During the fermentation period, the moisture contents of the four types of sauce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In other words, the reduced initial pH of the fish sauce and the reduction during fermentation intensified with treatment time. As we described previously, this initial pH reduction also occurs in the fermentation of fish sauce from a red snow crab C. japonicus with the addition of rice koji (Kim et al, 2015). Uchida et al (2005) reported the effects of soya sauce koji (Aspergillus oryzae) and lactic acid bacteria (Tretragenococcus halophilus) on the fermentation of fish sauce from a freshwater silver carp Hypophthalmichthys molitrix.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…In other words, the reduced initial pH of the fish sauce and the reduction during fermentation intensified with treatment time. As we described previously, this initial pH reduction also occurs in the fermentation of fish sauce from a red snow crab C. japonicus with the addition of rice koji (Kim et al, 2015). Uchida et al (2005) reported the effects of soya sauce koji (Aspergillus oryzae) and lactic acid bacteria (Tretragenococcus halophilus) on the fermentation of fish sauce from a freshwater silver carp Hypophthalmichthys molitrix.…”
Section: Resultssupporting
confidence: 63%
“…In other words, the reduced initial pH of the fish sauce and the reduction during fermentation intensified with treatment time. As we described previously, this initial pH reduction also occurs in the fermentation of fish sauce from a red snow crab C. japonicus with the addition of rice koji (Kim et al ., ). Uchida et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…(Ahn et al, 2014), (Ahn et al, 2006), (Baek et al, 2011), (Oh, 2007), (Lim et al, 2015;Kim et al, 2015a), (Kim et al, 2015b), (Kim et al, 2016), / (No andLee, 1995;Kim and Park, 1994), / (Chang et al, 1994), (Kim et al, 1999) , .…”
Section: 서 론mentioning
confidence: 99%